NiCo2O4 nanostructure-decorated PAN/lignin based carbon nanofiber electrodes with excellent cyclability for flexible hybrid supercapacitors. (6th December 2017) - Lei, Danyun; Li, Xiang-Dan; Seo, Min-Kang; Khil, Myung-Seob; Kim, Hak-Yong; Kim, Byoung-Suhk
Abstract: Nanostructured binary metal oxide-decorated carbon nanofibers (CNFs) were utilized as flexible electrodes for hybrid supercapacitor applications. Polyacrylonitrile (PAN)/lignin based carbon nanofibers (PAN/lignin CNFs) with different contents of lignin were prepared by electrospinning, stabilization and carbonization. Afterwards, the NiCo2 O4 oxides were deposited on the surface of CNFs by a facile hydrothermal method without any toxic reagents. SEM images confirmed that the NiCo2 O4 (nanosheet and nanoneedle) nanostructures were uniformly grown on the surface of every carbon fiber. The obtained flexible NiCo2 O4 -decorated PAN/lignin CNFs with 50% lignin (NiCo2 O4 @CNF55) electrode exhibited high specific capacitance of the ∼1757 F g −1 at 2 mA cm −2 and excellent cyclability with ∼138% capacitance retention after 5000 cycles at 7 mA cm −2, suggesting lower internal resistance and higher electrochemical reversibility. In addition, the NiCo2 O4 @CNFs//N-rGO solid state asymmetric supercapacitor devices were assembled in order to evaluate their practical applications. The NiCo2 O4 @CNF55//N-rGO asymmetric supercapacitor device exhibited a specific capacitance of 134.3 F g −1 at a current densities of 1 A g −1, and possessed a maximum energy density of 47.75 Wh kg −1 with a power density of 799.53 W kg −1 . Graphical abstract: Highlights: PAN/lignin-based carbon fibers were prepared by electrospinning, stabilization and carbonization. The NiCo2 O4 nanostructures were fabricated on PAN/lignin-based carbon nanofibers. The NiCo2 O4 -decorated fiber electrode exhibits highest specific capacitance of the ∼1757 Fg -1 . The NiCo2 O4 -decorated fiber electrode shows excellent capacitance retention of ∼138% after 5000 cycles.